Ketidakpatuhan Sudan Selatan dalam Skema Perjanjian Internasional R-ARCSS Terkait Keterlibatan Tentara Anak dalam Angkatan Bersenjata - Fithria, Farah Agnis (Universitas Jember, 2024)
This article aims to discover and understand the reasoning behind actor noncompliance with international agreements. In this case, the Government of South Sudan is not in compliance with international igreements relating to the involvement of child soldiers in the armed forces. International agreements seek to bind members to rules agreed upon by each party. This article discusses the R-ARCSS Agreement, signed by the two parties who previously clashed in the civil war in South Sudan and mediated by the UN and IGAD. This research examines the regulations that South Sudan does not comply with, especially regarding the involvement of child soldiers in the armed forces. The research question for this article is,